THE FUNCTION OF SHARIA MICROFINANCE INSTITUTIONS IN PROMOTING THE FINANCIAL INCLUSIVENESS AND THE REAL SECTOR (BMT NU JAWA TIMUR IN SUMENEP) - Aidi Faiz Romadoni; Sri Herianingrum (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
Poverty and inequality are classic problems. Financial institutions, in general, have not been able to alleviate it. The hope is for microfinance institutions. Included in this is the BMT NU Jawa Timur. For this reason, we have revealed the role of the Islamic microfinance institution in encouraging financial inclusiveness and the role of the Islamic microfinance institution in advancing the real sector. This research approach is qualitative with a case study strategy by using interviews and direct observation. The interviewees were the directors of BMT and customers. With a data analysis model from Hiles and Huberman, wherein analyzing the data, there are three steps taken. Namely, data reduction, data presentation and verification. The results of the study show that East Java BMT uses the term Lasisma which is commensurate with inclusive finance. The system is the same. Lasisma reaches out to the lowest levels of society. The BMT goes to community groups that need capital in developing unsecured businesses.Keywords: BMT NU Jawa Timur, Inclusive Finance, Lasisma, Real SectorREFFERENCE Arikunto, Suharsimi. (2002). Prosedur penelitian: Suatu pendekatan praktek. Jakarta: PT. Rineka Cipta.Asian Development Bank (ADB). (2011). Key indicators for Asia and the Pasific 2011: Framework for inclusive growth indicators, special supplement. Manila: ADB. Bakker, Anton dan Avhmad Choris Zubari. (1990). Metodologi penelitian filsafat. Yogyakarta: Kanisus.Bank Indonesia. (2014). Booklet financial inclusion. Jakarta: Bank Indonesia.Herianingrum, Sri dan Nurul Farida Damayanti. (2014). Pengaruh pembiayaan dana Baitul Mal wat Tamwil (BMT) Teladan terhadap kinerja usaha mikro di pasar semolowaru Surabaya. Jurnal Ekonomi Syariah Teori dan Terapan, 1(3), 194-204.Herianingrum, Sri., dan Abdul Muiz Hamid. (2014). Efektivitas target pembiayaan Baitul Maal Wa tamwil Surya Gemilang Desa Sedayu Lawas Kecamatan Brondong Kabupaten Lamongan. Jurnal Ekonomi Syariah Teori dan Terapan, 1(3), 119-127.Herianingrum, Sri dan Rohmah Diah Musdiana. (2015). Efektivitas pembiayaan mudharabah dalam meningkatkan kinerja UMKM (Studi kasus pada BMT Nurul Jannah Gresik). Jurnal Ekonomi dan Bisnis Islam, 1(1), 21-36.Subagyo, P. Joko. (1991). Metodologi penelitian teori dan praktik. Jakarta: Rhineka Cipta .Sumitra, Andri. (2009). Bank dan lembaga keuangan syariah. Jakarta: Prenada Media Group.